Analysis and Evaluation of Depth of Frozen Ground Affected by Road Climatic Conditions - Lina Juknevičiūtė; Alfredas Laurinavičius (The Baltic Journal of Road and Bridge Engineering)
Climatic factors are divided into more equable and more variable. More variable factors include a multi-year weather regime of a particular region or country. Climatic information, based on which climatic parameters and various quantitative indicators are calculated, is obtained from diferent sources. Primary meteorological information is the data obtained during the observations in meteorological stations. Another meteorological information especially important for road design, construction and maintenance is obtained from the Road Weather Information System (RWIS). Lithuania belongs to a number of countries experiencing a large effect of climatic conditions on road design, construction and repair. Climatic conditions is the amplitude and speed of temperature variation, temperature max and min, precipitation, wind direction and speed, thickness of snow cover, depth of such ground. One of the most important climatic factors in winter is a frozen ground. The depth of such ground depends on a negative temperature and its stability, thickness of snow cover and the start of its formation, vegetation, soil properties, composition, etc. The action of frost changes the structure of soil, affects the surface and underground water interchange, etc. Therefore, investigations and analysis of the change in the depth of frozen ground is important from both the theoretical and practical point of view.